Population Dynamics, Siderophore Production and Disease Suppression during Different Seasons of Pseudomonas aeruginosa from Acidic Paddy Fields - Sankar, Surabhi; Dileep, C. (International Journal of Scientific Research in Biological Sciences, 2020)
Applications of bio inoculants (PGPRs) are one of the most successful, non-chemicals, eco-friendly approach in agriculture. The bio inoculants were collected from the acidic paddy fields of Champakkulam in 3 different seasons. There were 120 strains isolated from the acidic conditioned paddy fields of Champakkulam. Among them KS1 is exhibited maximum zone of inhibition, siderophore production and root colonization than other strains and control. These were herbicide and pesticide resistant strains were used against domestic phyto pathogen. Root colonization of these bacterial strain showing various changes on these different seasons .In summer season strain produced maximum absorbance in UV mediated spectrophotometry .KS1 (MK 894011) ,PS2 (MK 894012), PS3 (MK 894013), RS1 (MK 894010), KNP (MK 894014) were identified as Pseudomonas aeruginosa by biochemical characterization as well as 16 s ribosomal RNA sequence. Data were subjected to t-test, and ANOVA. All treatments are compared with FPO4 (KF500003).The experiments having 5 replicates in each treatments. This study mainly focused on antagonistic effect, siderophore production, disease resistance and root colonization different seasons in different area of Champakkulam village.